Age at First Drink, Drinking, Binge Drinking, and DSM‐5 Alcohol Use Disorder Among Hispanic National Groups in the United States. (1st April 2014) - Caetano, Raul; Mills, Britain A.; Vaeth, Patrice A. C.; Reingle, Jennifer
<x xml:space="preserve">Abstract</x> Background This article examines age at first drink and adult drinking, binge drinking and DSM‐5 alcohol use disorder (AUD) among U.S. Hispanic national groups. Methods Respondents come from 2 independent studies. The Hispanic Americans Baseline Alcohol Survey used a multistage cluster sample design to interview 5, 224 individuals 18 years of age and older selected from the household population in Miami, New York, Philadelphia, Houston, and Los Angeles. Respondents in the border area (N = 1, 307) constituted a household probability sample of Mexican Americans living on U.S. counties that border Mexico. In both surveys, data were collected during computer‐assisted interviews conducted in respondents' homes. The Hispanic American Baseline Alcohol Survey and the border sample response rates were 76 and 67%, respectively. Results U.S.‐born Hispanics begin drinking at a younger age than those who are foreign‐born, independent of national group. Among foreign‐born Hispanics, age of arrival in the United States is not associated with age at first drink. Results support the hypothesis that a younger age at first drink is associated with a higher mean volume of drinking, a higher probability of bingeing, and a higher probability of DSM‐5 AUD. But the results do not show a clear pattern by which a particular national group would consistently show no associations or stronger associations between age at first drink and the alcohol‐related outcomes under consideration. Conclusions An earlier age at first drinking is positively associated with heavier drinking patterns among U.S. Hispanics. However, as in other areas of alcohol epidemiology, here too there is considerable variation in age at first drink and drinking across Hispanic national groups.